Analysis of real-world data for medical device evaluation: Chinese manual - A. R. Kasimova; Wenlong Zhao (Реальная клиническая практика: данные и доказательства, 2024)
Real-word data obtained using medical devices differ from the use of drugs. When using medical devices, the effectiveness is usually not in doubt, and the issues of biocompatibility, safety, and long-term use come to the fore. This article presents a translation of the clinical guidelines of the People’s Republic of China on planning and conducting studies on the use of medical devices in real-world clinical practice, as well as statistical processing of the information obtained in an abbreviated form.